Порівняльний аналіз вад слуху школярів відповідно до встановлених педагогічних і медичних класифікацій - Маслова, Олена Володимирівна; Гопей, Максим Миколайович; Maslova, Olena; Gopey, Maksim (Східноєвропейський національний університет імені Лесі Українки, 2016)
Необхідність диференціації контингенту дітей, які мають порушення слуху, тісно повʼязана з практикою побудови медичних і педагогічних типологій дітей зі встановленими порушеннями слуху. Питання дослідження та класифікації залишкової слухової функції в дітей із дефектами слуху здавна цікавили як лікарів-оториноларингологів (отіатрів), так і педагогів. Створені педагогічні класифікації адресовані вчителю й спрямовані на обґрунтування різних підходів до навчання осіб із вадами слуху. Медичні класифікації мають на меті дати оториноларингологам орієнтири для проведення лікування та профілактики захворювань, що призводять до погіршення слуху. У статті представлено результати дослідження класифікацій порушень слуху, їх систематизації та комплексного застосування. The necessity of differentiation a contingent that has hearing disorders is closely associated with the practice of formation of medical and teaching typologies of children with hearing impairments. Issues of research and classification of residual hearing function of children with hearing defects were always interesting to doctors-otolaryngologists (otologists), and pedagogues. The aim of our study is conducting the comparative analysis of pupils with hearing defects in accordance with established educational and medical classifications. Objectives of the study: to systematize the existing classification of hearing impairments; to describe the installed impaired hearing of pupils in accordance with the systematic classification of hearing impairments. The created pedagogical classifications are addressed to a teacher and are aim at studying various approaches to teaching hearing impaired persons. Medical classifications give some guidelines to otolaryngologists for treatment and prevention of diseases that lead to hearing loss. The article presents the results of studying the classifications of hearing loss, their systematization and complex application.
Comparative Analysis of Hearing Impaired Schoolchildren According to the Established Pedagogical and Medical Classifications
Keywords: класифікація; вада слуху; порушення слуху; діти; школярі; слабочуючі; приглухуватість; глухота; classification; hearing impairment; children; pupils; hearing-impaired; hearing loss; deafness